A Cyber-Based Data-Enabled Virtual Organization for Wind Load Effects on Civil Infrastructures: VORTEX-Winds - Kareem, Ahsan; Kwon, Dae Kun (Frontiers in Built Environment, 2017)
Despite many advances in the area of wind effects on structures in recent decades, research has been traditionally conducted within limited resources scattered geographically. With the trend toward increasingly complex designs of civil infrastructure combined with the escalating potential for losses by extreme wind events, a new culture of research needs to be established based on innovative and collaborative solutions for better management of the impact of extreme wind events. To address this change, this paper presents a new paradigm of a multi-scale cyber based laboratory framework for the analysis/design, modeling and simulation of wind load effects based on an ongoing collaborative cyberinfrastructure based platform, VORTEX-Winds: Virtual Organization for Reducing the Toll of EXtreme Winds (https://vortex-winds.org), and discusses its current status since its inception in 2007 and ongoing developments. This collaborative framework as it evolves would enable a paradigm shift by offering advanced cyber-enabled modules (e-modules) for accelerating advances in research and education to achieve improved understanding and better modeling of wind effects on structures. Accordingly, it will enhance wind community’s analysis and design capabilities to address next generation challenges posed by wind. Through empowering those without computational or experimental resources, the e-modules will encompass a large set of subject areas and topics categorized as Database-enabled design, Full-scale/Field site data repository, Statistical/Stochastic toolboxes, Tele-experimentation, Uncertainty modeling, Damage assessment, and Computational platforms. This prototype will allow access to the individual e-module, while it is envisaged that next level of development in VORTEX-Winds will have the capability for an automated and integrated analysis/design through a nexus of e-modules. A highlight of the e-modules currently completed or in development is presented not only to show the efficacy of the framework to enhance and supplement the limitation of traditional off-line approaches, but also to describe architecture and features of e-modules to promote additional cyber-enabled data-driven developments in the field.